Influence of MoO3 on the Structure of Lithium Aluminum Phosphate Glasses - SADDEEK, Yasser B.; ABO-NAF, S. M. (Archives of Acoustics, 2012)
IR spectroscopy, density and ultrasonic velocity measurements have been carried out for aluminum lithium phosphate glasses with and without MoO3. The observed changes in the FTIR spectra of the glasses were related to the modifier/former role of molybdenum ions. The results revealed that the density increases with increasing MoO3 content, which was attributed to the increase in the compactness and packing of the glass network. The ultrasonic data were analyzed in terms of creation of new bonds of MoO3 attached to phosphate units. The new bonds increased the average crosslink density and the number of network bonds per unit volume along with a strengthening of the different modes of vibrations which in its turn increased the ultrasonic velocity, the rigidity and hence the elastic moduli of the glasses.